Guidelines for Applying Cohesive Models to the Damage Behaviour of Engineering Materials and Structures - Schwalbe, Karl-Heinz; Scheider, Ingo; Cornec, Alfred (SpringerBriefs in Applied Sciences and Technology,, 2013)
This brief provides guidance for the application of cohesive models to determine damage and fracture in materials and structural components. This can be done for configurations with or without a pre-existing crack. Although the brief addresses structural behaviour, the methods described herein may also be applied to any deformation induced material damage and failure, e.g. those occurring during manufacturing processes. The methods described are applicable to the behaviour of ductile metallic materials and structural components made thereof. Hints are also given for applying the cohesive model to other materials.